Analisis Hukum Islam Terhadap Jual Beli Emas Secara Tidak Tunai - Armen, Rio Erismen (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
This study aims to analyze whether gold can be classified as money or not from the perspective of Islamic law. The study uses descriptive qualitative method through library study and interviews as the data collection techniques. The results exposed the view of Islamic law on gold and its utility as the medium of exchange that is portrayed from various sides, namely: characteristics, function, and arguments (al-adillah) that define gold as the commodity meeting the characteristics of money. This is also backed by the opinions of economists and Sharâ€˜Ä«ah scholars (fuqahÄ) regarding al-â€˜illat of gold. The study concluded that the sale and purchase transaction of gold should be in cash (naqdan) which is analogous to currencies exchange transaction (â€˜aqd al-sharf) that is not allowed to be in the form of installment transaction.